Persepsi Penyuluh Terhadap Pentingnya Peran Penyuluhan Perkebunan Kelapa Sawit Di Kecamatan Tapung Kabupaten Kampar - Sahera, Lini Syilva; sayamar, Eri; ', Rosnita (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2014)
Research abaout agricultural extension field perceptions for the importance the role of extension oil palm plantations in Tapung District Kampar purpose is (1) To determind the organizing of extension oil palm plantation in Tapung District Kampar Regency. (2) To determind the agricultural extension field perceptions for the importance the role of extension oil palm plantations . Research with method of survey and intake of sampel all extension in District Tapung amounting to 5 people and held an interview with as respondent, data analysis use Scale Likert'S Summated Rating ( SLR). Variable role of extension agent the used according to Mardikanto (2009) and UU SP3K Year 2006 . The result illustrate organizing of extension in Tapung District has gone well according the element of extension. Extension workers perceive that the role of education is important for oil palm plantations can be seen from the non-farmers : 1. Facility process study get score 4,14 with important category 2. Amenity access to get score 4,22 with very importent category. 3. Ability of leadership get score 3,98 with important category 4. Developing organizational get score 4,28 with very importan category 5. Analysing and solving problem to get score 4,35 with very important category 6. Developing awareness get score 4,48 with important category 7. Institutionalizing cultural values get score 4,12 with important category 8. Supervision or construction get score 4,63 with very important category 9. Evaluation to get score 4,20 with very important category .   Keywords: agricultural extension field perceptions, the importance of role  extension, palm oil